Weisheng-tang protects against ischemic brain injury by modulating microglia activation through the P2Y12 receptor - Min Jae Kim; Min Jae Kim; Dohee Lee; Dohee Lee; Ji Hye Ryu; Ji Hye Ryu; Seo-Yeon Lee; Byung Tae Choi; Byung Tae Choi; Byung Tae Choi; Young Ju Yun; Hwa Kyoung Shin; et al. (Frontiers Media S.A., 2024)
Background: Stroke, a leading cause of death and disability, lacks effective treatments. Post-stroke secondary damage worsens the brain microenvironment, further exacerbating brain injury. Microglia's role in responding to stroke-induced damage in peri-infarct regions is crucial. In this study, we explored Weisheng-tang's potential to enhance ischemic outcomes by targeting microglia.Methods: We induced middle cerebral artery occlusion and reperfusion in mice, followed by behavioral assessments and infarct volume analyses after 48 h, and examined the changes in microglial morphology through skeleton analysis.Results: Weisheng-tang (300 mg/kg) significantly reduced infarction volume and alleviated neurological and motor deficits. The number of activated microglia was markedly increased within the peri-infarct territory, which was significantly reversed by Weisheng-tang. Microglial morphology analysis revealed that microglial processes were retracted owing to ischemic damage but were restored in Weisheng-tang-treated mice. This restoration was accompanied by the expression of the purinergic P2Y12 receptor (P2Y12R), a key regulator of microglial process extension. Weisheng-tang increased neuronal Kv2.1 clusters while suppressing juxtaneuronal microglial activation. The P2Y12R inhibitor-ticagrelor-eliminated the tissue and functional recovery that had been observed with Weisheng-tang after ischemic damage.Discussion: Weisheng-tang improved experimental stroke outcomes by modulating microglial morphology through P2Y12R, shedding light on its neuroprotective potential in ischemic stroke.